The Impact of the Inflow of Ukrainian Refugees on Poland’s Labor Market : Workforce Integration and its Influence on the Wages - Pashutin, Pavlo (2025)
This bachelor's thesis explores the impact of the Ukrainian refugees on the labour market in Poland, focusing on the integration of the workforce and its influence on the average wages across regions of Poland. The study investigates how the movement of refugees, caused by the full-scale Russian military invasion of Ukraine, changed the labour dynamics of Poland, one of the countries that hosted the most refugees on its territory. Using a panel data analysis from 2017 to 2023, the research examines the correlation between refugee density and average wages across Polish regions, incorporating control variables such as GDP per capita and unemployment rate. To assess the impact of factors that vary across dimensions, several fixed-effect models were used. This work provides a quantitative assessment of the relationship between migration processes and economic indicators in times of crisis, offering analytical insights that may inform future research and guide governmental policy in the areas of labour market and refugee integration